Social psychology of social problems : the intergroup context - Golec, Agnieszka; Cichocka, Aleksandra (Palgrave Macmillan, 2013)
"Encompassing contemporary social problems and cutting-edge research, top international experts provide a window into understanding the psychology behind societal problems and why they develop, offering crucial applications of psychological theory for the undergraduate student."--Publisher's website.